Pharmacokinetic modeling of subcutaneous heroin and its metabolites in blood and brain of mice. (11th April 2011) - Boix, Fernando; Andersen, Jannike M.; Mørland, Jørg
ABSTRACT High blood–brain permeability and effective delivery of morphine to the brain have been considered as explanations for the high potency of heroin. Results from Andersen et al. indicate that 6‐monoacetylmorphine (6‐MAM), and not morphine, is the active metabolite responsible for the acute effects observed for heroin. Here, we use pharmacokinetic modeling on data from the aforementioned study to calculate parameters of the distribution of heroin, 6‐MAM and morphine in blood and brain tissue after subcutaneous heroin administration in mice. The estimated pharmacokinetic parameters imply that the very low heroin and the high 6‐MAM levels observed both in blood and brain in the original experiment are likely to be caused by a very high metabolic rate of heroin in blood. The estimated metabolic rate of heroin in brain was much lower and cannot account for the low heroin and high 6‐MAM levels in the brain, which would primarily reflect the concentrations of these compounds in blood. The very different metabolic rates for heroin in blood and brain calculated by the model were confirmed by in vitro experiments. These results show that heroin's fast metabolism in blood renders high concentrations of 6‐MAM which, due to its relatively good blood–brain permeability, results in high levels of this metabolite in the brain. Thus, it is the high blood metabolism rate of heroin and the blood–brain permeability to 6‐MAM, and not to heroin, which could account for the highly efficient delivery of active metabolites to the brain after heroin administration.